Impact of formal credit and social capital on the scalability of agricultural operations - Deng-Feng Wei; Yi-Feng Zhang (Scientific Reports)
Abstract Moderate-scale farmland operations are pivotal for boosting agricultural productivity and sustainability. This study uses a moderated mediation model to explore the impact of formal financial credit, social capital, and crop diversity on these operations. Analyzing data from 985 farming households in Shandong Province, we discover that access to formal credit enhances the propensity for larger-scale farming by facilitating land resource inflow, with family farms mediating 38.59% of this effect. However, strong social capital and the cultivation of fruits and vegetables negatively modulate this mediation, indicating intricate dynamics that moderate the benefits of financial support. This research sheds light on the complex mechanisms of rural revitalization, emphasizing the interplay among financial resources, community dynamics, and agricultural choices.